THE SUCCESSFUL OF THEO-DEMOCRACY IN IRAN: SPIRIT OF NEO-REVIVALISM TO BE ISLAMIC REPUBLIC ROLE MODEL - Muhammad Haizul Falah; Liza Umami (IAIN Bone, 2022)
The Islamic Republic of Iran is a case study of the rise of Muslims inspired by the Islamic Neo-Revivalism movement which views that westernization and modernization are considered to have failed in responding to the political challenges of corruption, economic decline, social injustice, and spiritual malaise, such as the pre-Islamic period. After the success of the 1979 Iranian revolution, it was a turning point in the political and security constellations of Iran and the West which resulted in the emergence of collective inspiration from Muslims around the world for Iran's persistence in implementing theo-democracy principles which the West considered as a setback. This paper is an analytical study using a qualitative-descriptive approach. The results of this study regarding on Iran's theocracy and democracy principles, proved of the successful; a) public participation in politics; b) fulfillment of the rights of women and minorities; c) freedom of the press; d) effectiveness of general elections; e) a puralistic political party system; f) good governance.